The Nigerian judge - Tobi, Niki, 1940- ([Nigeria] : A & T Professional Publishers, 1992)
Deals with the conditions of service, judiial ethics, jurisdiction and judicial powers, the hearing and the determination of matters, the Nigeian judge's relationship with the bar and the Government and the public.
Includes bibliographical references and indexes.
oif 04/03/15
Loan
Keywords: Judges -- Nigeria; Judicial process -- Nigeria